QUALITY OF LIFE AMONG LOWER LIMB PROSTHESIS USERS ATTENDING ARTIFICIAL LIMB CENTER OF FAUJI FOUNDATION HOSPITAL RAWALPINDI: Prosthesis Users And Quality of Life - Amjad, Dr Tahira; Umay Kalsoom, Umay Kalsoom; Bairam, Saima (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess quality of life and the influencing factors as perceived by lower limb prosthesis users.Study Design: Cross sectional study.Place and Duration of Study: Artificial Limb Centre, Fauji Foundation Hospital Rawalpindi, 11 months (Jan toNov 2014).Material and Methods: A sample of 50 patients with lower limb amputations and using lower limb prosthesiswere recruited by applying inclusion criteria. Responses were recorded on demographic variables, reasons foramputation, time of provision of prosthesis, employment status etc. by the investigator on a structured pretestedquestionnaire after their consent. A p-value of